2018
DOI: 10.1136/ejhpharm-2017-001449
|View full text |Cite
|
Sign up to set email alerts
|

Junior doctors’ communication with hospital pharmacists about prescribing: findings from a qualitative interview study

Abstract: ObjectivesTo explore factors affecting communication between Foundation Year (FY) 1 doctors and hospital pharmacists about prescribing from the junior doctors’ perspective.MethodsTrained interviewers (n=4) conducted semistructured interviews with FY1 doctors who were purposively sampled from three hospitals in England. FY1 doctors were asked about their experiences of communication with hospital pharmacists about their prescribing; instances where they disagreed with or did not implement a hospital pharmacist’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…Interestingly, MBBS students were more likely compared with MPharm students to find the support of pharmacists useful to them, perhaps in acknowledgement of the medicines expertise of pharmacists. 21 We consider that our bottom-up approach to education around medication review and deprescribing, and other educational strategies should be complemented by continuing to acknowledge barriers to deprescribing and how senior clinicians can, where appropriate, seek to overcome them. The outcomes of our study will include an undergraduate IPE on medication review at King’s College London.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MBBS students were more likely compared with MPharm students to find the support of pharmacists useful to them, perhaps in acknowledgement of the medicines expertise of pharmacists. 21 We consider that our bottom-up approach to education around medication review and deprescribing, and other educational strategies should be complemented by continuing to acknowledge barriers to deprescribing and how senior clinicians can, where appropriate, seek to overcome them. The outcomes of our study will include an undergraduate IPE on medication review at King’s College London.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that greater access to pharmacists and shared decision making improved communication between health care professionals. 20 As such, telepharmacists can offer a range of clinical interventions related to adherence, safety, gaps in care, vaccines, and cost savings, further illustrating their value to telehealth teams in caring for patients with multiple conditions, including epilepsy. 13 Despite the considerable number of recommendations made by the telepharmacist, the majority failed to align with any HEDIS measures.…”
Section: Demographic Characteristics Of Study Participants (N = 86)mentioning
confidence: 99%
“… 21 , 32 The impact of these gaps in training are further underscored amidst growing public attention on bed crises, overcrowding, and mounting waiting times. 21 , 39 42 …”
Section: Introductionmentioning
confidence: 99%
“…21,32 The impact of these gaps in training are further underscored amidst growing public attention on bed crises, overcrowding, and mounting waiting times. 21,[39][40][41][42] With a consistent approach to IPC training in EM continuing to elude practice, [43][44][45][46] and guided by the importance placed upon it by the Accreditation Council for Graduate Medical Education (ACGME) 20,23 and the Institute of Medicine, 11,25,26,[47][48][49][50] we seek to evaluate regnant accounts of IPC training in EM to attend to this gap in understanding 27,51 and guide efforts to design a setting specific training approach. 11,[52][53][54][55]…”
Section: Introductionmentioning
confidence: 99%